Prevention of Cervical Cancer With Seminar and IVA Test for Productive Ages Women In Universitas Negeri Padang - Elsa Yuniarti; Rahmawati Darrussyamsu; Moralita Chatri (Fakultas MIPA Universitas Negeri Padang, 2020)
Cervical cancer is one of the main problems of reproductive health in women in Indonesia. The results of a questionnaire of 100 women of productive age workers in UNP 80% had never done an IVA test and did not know about the IVA test for early detection of cervical cancer. Lack of knowledge and awareness of women workers at UNP to take preventive measures for early detection of cervical cancer, is carried out in prevention of cervical cancer with seminar and IVA test for productive ages women in Universitas Negeri Padang. Activities have been carried out in the rector's office, faculties and IVA test at the UNP polyclinic in collaboration with the Air Tawar Health Center, Padang City Health Office and the UNP Polyclinic. This activity has 3 stages namely seminar the importance of early detection of cervical cancer, IVA test and monitoring. Participants are women of childbearing age over the age of 18 who are married / widowed, not yet married but have had sexual intercourse at UNP. Seminar participants totaling 130 participants have exceeded the 30% target. Monitoring activities are carried out with questionnaires to participants through a Google form sent to participant WhatsApp. The questionnaire contained aspects of knowledge and attitudes of participants towards early detection of cervical cancer. The results obtained 88.40% knowledge aspects (very good) and 84.16% attitude (good). But the participation for IVA test is still less than 10%. With this activity increased knowledge and active role of women for preventive action with early detection of cervical cancer that aims to improve the quality of health and reduce the mortality rate of Indonesian women against cervical cancer.